Avaliação das inclinações dentárias de casos tratados com braquetes autoligáveis por meio da Tomografia Computadorizada de Feixe Cônico (TCFC) - Rhoden, Fernando Kleinübing (2015)
This study was to evaluate the changes in dental inclinations in anterior teeth, including canines, from orthodontic treatment with self-ligating brackets. The sample consisted of 20 patients with a mean age of 16 years and 5 months (SD: 5y 11m), 12 (60%) were females and 8 (40%) were male, facial pattern I, Brazilians, with permanent dentition and malocclusion class I and medium crowding in the upper arch of 7,38mm (SD: 3,94mm) and lower 6,76mm (SD: 2,36mm), treated with selfligating brackets passive (Smart Clip, MBT prescription - 3M, Monrovia, USA) without wear and without extractions. Was adopted the following sequence of nickel titanium wire termoativado: 0.014 ", followed by 0.016", 0.016 "x 0.022", 0.019 "x 0.025" and ending with the wire 0.019 "x 0.025" stainless steel. Each wire was maintained for at least 10 weeks. The CBCT and dental casts was obtained in two moments prior to the installation of corrective orthodontic appliances (moment 1) and the end of the aligning and leveling with rectangular wire 0.019 "x 0.025" steel (moment 2). The DICON images were measured with InVivoDental Aplication Version 5.3.1 software (Anatomage, San Jose, CA) and dental casts measured with a digital caliper Mitutoyo, 0.01mm precision. The average buccal inclination obtained by the upper central incisors was 6,55o and 7.24o for the lower. The upper and lower lateral incisors on the movement of the central incisors, ranging from 4,90o and 8,72o respectively. The lower canines accompanied the positive slope of the central and lateral incisors, with average inclination of 3,88o, which showed an average increase of 1,96mm in Intercanine distance. The upper canines showed a negative inclination, varying the right and left side between the -0,22o -0,50o, respectively, with a mean change in 0,82mm Intercanine distance, keeping negative correlation between crowding and Intercanine initial distance. Orthodontic treatment protocol with selfligating brackets in patients with crowding treated without extraction and / or wear, prints increments on the buccal inclination of the upper and lower incisors in similar amounts and symmetrically without keeping correlation with the amount of crowding present at the beginning of treatment. The CBCT, together with the dental casts, more consistently showed that Intercanine distance tends to increase very little (upper and lower 1,96mm = 0,82mm). The inclination of the canines was different when compared to the upper arch (Right: -0,22o; Left -0,55o) with the lower (3,88o). Therefore the upper canine tooth take on characteristic "pillar" to the movement of other teeth, keeping a negative correlation to with the crowding and the Intercanine distance.